Outskirts : queer experiences on the fringe - Compton, D'Lane R. (D'Lane Rebecca), 1977-; Stone, Amy L. (New York University Press, 2024)
"Outskirts is an edited volume from sociology scholars that addresses the complexity of the queer experience in diverse spaces, places, and identities in the United States"--